The sustainable enterprise profiting from best practice - Brown, Christopher Stephen; Gale Group (London Kogan Page, 2005)
Aims to assist those running or advising organizations of all types and sizes in understanding the business case for sustainable development and corporate social responsibility. Tackles the subject from many different perspectives; offering advice and guidance in preparing and implementing programs and policies appropriate for the different contexts in which businesses operate.
Part 1: Sustainable value -- Part 2: A new framework for business -- Part 3: Business standards -- Part 4: Marketing and consumption -- Part 5: Waste and recycling -- Part 6: Emissions and contaminants -- Part 7: Land use -- Part 8: Energy use -- Part 9: Transport -- Part 10: Health and safety -- Part 11: Employment -- Part 12: External relationships -- Part 13: Process efficiency -- Part 14: Funding and investment -- Part 15: Making it happen.
Electronic reproduction.
Keywords: Social responsibility of business; Business enterprises -- Environmental aspects; Small business -- Environmental aspects; Industrial management; Factory and trade waste -- Environmental aspects; Pollution prevention; Business ethics; Electronic books